Enhanced Antimicrobial, Cytotoxicity, Larvicidal, and Repellence Activities of Brown Algae, Cystoseira crinita-Mediated Green Synthesis of Magnesium Oxide Nanoparticles - Fouda, Amr; Eid, Ahmed M.; Abdel-Rahman, Mohamed Ali; EL-Belely, Ehab F.; Awad, Mohamed A.; Hassan, Saad El-Din; AL-Faifi, Zarraq E.; Hamza, Mohammed F. (Frontiers in Bioengineering and Biotechnology, 2022)
Herein, the metabolites secreted by brown algae, Cystoseira crinita, were used as biocatalyst for green synthesis of magnesium oxide nanoparticles (MgO-NPs). The fabricated MgO-NPs were characterized using UV-vis spectroscopy, Fourier transforms infrared spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy linked with energy-dispersive X-ray (SEM-EDX), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Data showed successful formation of crystallographic and spherical MgO-NPs with sizes of 3–18 nm at a maximum surface plasmon resonance of 320 nm. Moreover, EDX analysis confirms the presence of Mg and O in the sample with weight percentages of 54.1% and 20.6%, respectively. Phyco-fabricated MgO-NPs showed promising activities against Gram-positive bacteria, Gram-negative bacteria, and Candida albicans with MIC values ranging between 12.5 and 50 μg mL−1. The IC50 value of MgO-NPs against cancer cell lines (Caco-2) was 113.4 μg mL−1, whereas it was 141.2 μg mL−1 for normal cell lines (Vero cell). Interestingly, the green synthesized MgO-NPs exhibited significant larvicidal and pupicidal activity against Musca domestica. At 10 μg mL−1 MgO-NPs, the highest mortality percentages were 99.0%, 95.0%, 92.2%, and 81.0% for I, II, III instars’ larvae, and pupa of M. domestica, respectively, with LC50 values (3.08, 3.49, and 4.46 μg mL−1), and LC90 values (7.46, 8.89, and 10.43 μg mL−1), respectively. Also, MgO-NPs showed repellence activity for adults of M. domestica at 10 μg mL−1 with 63.0%, 77.9%, 84.9%, and 96.8% after 12, 24, 48, and 72 h, respectively.